Photosynthetic plasticity of Nothofagus pumilio seedlings to light intensity and soil moisture - Martínez Pastur, Guillermo José; Lencinas, María Vanessa; Peri, Pablo Luis; Arena, Miriam Elizabeth (Elsevier, 2025)
Nothofagus seedlings often survive and grow slowly for a long time in the shaded understory. This creates a seedling bank with a potential advantage in reestablishing canopy disturbances. To manage primary forests more effectively, it is important to understand the basis of plant regeneration ecophysiology, and their plasticity to changes in environmental factors. The objective was to evaluate the photosynthetic plasticity of Nothofagus pumilio seedlings to light intensity and soil moisture gradients; and to relate them with silvicultural prescriptions. Six treatments with three light intensities (4, 26 and 64% of the natural incident irradiance) and two soil moistures levels (40–60 and 80–100% soil capacity) were assayed under greenhouse controlled conditions. CO2 gas exchanges were measured every month on seedlings growing in each condition. In the shaded treatments seedlings grow below their optimum photosynthetic potential (leaf light-saturated net photosynthesis rate of 5.1 μmol CO2 m−2 s−1) compared with the lighted treatments by improving their photosynthetic performance (8.3–8.4 μmol CO2 m−2 s−1). Seedling growing under low soil moisture conditions had higher leaf light-saturated net photosynthesis rate than plants grown under 80–100% soil water capacity (7.8 and 6.6 μmol CO2 m−2 s−1, respectively). When light (up to 150–200 μmol m−2 s−1) and soil moisture (40–60% soil capacity) levels were favourable, seedling plants could exhibit their maximum photosynthetic capacity. If one of these factors became limiting, the plants reduced their photosynthetic rate, e.g. N. pumilio seedlings with enough light and high levels of soil moisture, probably decreased their growth and fine roots activity. For this, application of silviculture systems must take into account the changes in both factors (light and soil moisture) for maximize the growth potential in the natural regeneration. These findings must be combined with morphological variables at a whole-plant, shoot, crown and leaf levels to determine the optimum growth conditions.